MENINAS DIGITAIS NA COMPUTAÇÃO - UNIJUI - LUIZ PADOIN , EDSON; ZANFRA SERENO , FERNANDA; SCHREIBER PADILHA , JOCEMARA; KALAITZIS GONZAGA , SABRINA (Salão do Conhecimento, 2020)
Projeto de extensão UNIJUI